2018
DOI: 10.1176/appi.ps.201700283
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Incorporating Peer-to-Peer Interactions Into Digital Interventions for Psychotic Disorders: A Systematic Review

Abstract: Objective Peer-to-peer interactions and support groups mitigate experiences of social isolation and loneliness often reported by individuals with psychotic disorders. Online peer-to-peer communication can promote broader use of this form of social support. Peer-to-peer interactions occur naturally on social media platforms, but they can negatively affect mental health. Recent digital interventions for persons with psychotic disorders have harnessed the principles of social media to incorporate peer-to-peer com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 74 publications
(136 reference statements)
0
50
0
1
Order By: Relevance
“…However, dependent on the trial outcomes, there are several target areas for further innovation which may involve additional behaviour change methods and technologies (e.g. embodied conversational agents, online support groups, instant messaging, wearable biofeedback and gameification) [68][69][70][71]. From an agile science perspective, SlowMo could be implemented as a module within a broader digital therapy platform for psychosis [42,72] or adapted for a range of other difficulties and settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, dependent on the trial outcomes, there are several target areas for further innovation which may involve additional behaviour change methods and technologies (e.g. embodied conversational agents, online support groups, instant messaging, wearable biofeedback and gameification) [68][69][70][71]. From an agile science perspective, SlowMo could be implemented as a module within a broader digital therapy platform for psychosis [42,72] or adapted for a range of other difficulties and settings.…”
Section: Discussionmentioning
confidence: 99%
“…• Individuals with mental disorders can connect with care providers and access evidence-based services • Online peer support augments existing interventions to improve client engagement and compliance • Peer networks increase social connectedness and empowerment during recovery • Interactive peer-to-peer features of social media appear beneficial for social functioning • Mobile apps offer potential to monitor symptoms, prevent relapses and help users set goals • Digital peer-based interventions are feasible and acceptable for targeting fitness and weight loss in people with mental disorders • Online networks can extend support to caregivers of those with mental disorders (Alvarez-Jimenez et al 2013Aschbrenner et al 2018aAschbrenner et al , 2016bBiagianti et al 2018;Birnbaum et al 2017b;Gleeson et al 2017;Lal et al 2018;Naslund et al 2016bNaslund et al , 2018Schlosser et al 2016Schlosser et al , 2018 Challenges 1) Impact on symptoms…”
Section: Facilitate Social Interactionmentioning
confidence: 99%
“…With the widespread use of social media among individuals living with mental illness combined with the potential to facilitate social interaction and connect with supportive peers, as summarized above, it may be possible to leverage the popular features of social media to enhance existing mental health programs and services. A recent review by Biagianti et al (2018) found that peer-to-peer support appeared to offer feasible and acceptable ways to augment digital mental health interventions for individuals with psychotic disorders by specifically improving engagement, compliance, and adherence to the interventions and may also improve perceived social support (Biagianti et al 2018).…”
Section: Promote Engagement and Retention In Servicesmentioning
confidence: 99%
“…Interventions focusing on social network maintenance and enhancement have also been applied and found to be useful to combat loneliness 20. Social interventions could be combined with the application of technology such as online peer-to-peer interactions and support groups through social media platforms to alleviate loneliness especially in persons with psychotic disorders 35. However, loneliness in older people can create serious problems that could not be alleviated with the social support only32; other types of interventions are required such as technological interventions (eg, digital applications (apps), online social networks and social robots) to enhance emotional support and social interaction 36…”
Section: Introductionmentioning
confidence: 99%